Indian J Pharm Sci 2020
DOI: 10.36468/pharmaceutical-sciences.673
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Activity of Slime Extract from Giant African Snail (Lissachatina fulica)

Abstract: The present study aims to investigate the antiinflammatory activity of the slime extracts from the giant African snail, Lissachatina fulica. In this study, aqueous and ethanol extracts of the snail slime were evaluated for antiinflammatory activities in vitro. The aqueous extract showed greater antiinflammatory activities than the ethanol extract. The aqueous extract was further tested for antiinflammatory activity in vivo. For acute inflammation, the ear oedema assay was used to screen the slime extract. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…of C. arvensis and their loaded Alg-Cs/NPs exhibited non-hemolytic activities (percent hemolysis, 3–12%) even at maximum concentration of 1000 µg/ml. The work’s outcomes concurred with those of the earlier investigation reported by Wiya et al [ 59 ]. They stated that the hemolytic effect of the both the aqueous and ethanolic slime extracts ranged from 7.01 ± 0.54 to 13.42 ± 0.28%.…”
Section: Discussionsupporting
confidence: 89%
“…of C. arvensis and their loaded Alg-Cs/NPs exhibited non-hemolytic activities (percent hemolysis, 3–12%) even at maximum concentration of 1000 µg/ml. The work’s outcomes concurred with those of the earlier investigation reported by Wiya et al [ 59 ]. They stated that the hemolytic effect of the both the aqueous and ethanolic slime extracts ranged from 7.01 ± 0.54 to 13.42 ± 0.28%.…”
Section: Discussionsupporting
confidence: 89%
“…In other researches, the mucus obtained from giant African snail, Lissachatina fulica, has shown also promising anti-inflammatory potential both by in vivo tests and by in vitro tests [59]. Following the analysis performed, Sri Harti et al concluded that improving an inflammatory status with a preparation based on the combination of snail mucus and chitosan may be an alternative to synthetic compounds [60].…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, in previous but recent researches, the extraction of snail slime still led to the killing of the animals. Wiya et al extracted the snail slime by placing the snails on a plate in warm (32 °C) water and then scrubbing the outer shell and slime was squeezed from the animal, leading to animal death [ 64 ]. Similarly, Onyema and Adikwu, both extracted the snail slime by mechanically removing the outer shell and then scrubbing the fleshy animal, leading to their death [ 65 , 66 ].…”
Section: Snail and Slug Slime Extraction Methodsmentioning
confidence: 99%